Incidence of hypertensive disorders of pregnancy and it’s maternal-fetal outcome in admitted antenatal patients in tertiary care centre, Bhilai, Chhattisgarh, India - Singh, Pooja; Khandasu, Seema; Ratnani, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Pre-eclampsia refers to any new onset of hypertension and proteinuria after 20 weeks of gestation in a previously normotensive, non proteinuric women. Hypertension is a very common medical complication of pregnancy. It is one of the leading causes of maternal and fetal mortality and morbidity worldwide. Early detection, close surveillance and timely delivery are necessary to reduce complications and improvement in maternal and fetal health and outcome. To determine the incidence, risk factors and maternal and fetal outcomes in women with hypertensive disorders of pregnancy in all pregnant women attending Obstetrics and Gynaecology department, Shanakaracharya Institute of Medical Science, Bhilai. Methods: This is a retrospective record-based observational study conducted over a period of one year from January 2020-December 2020 after getting approval from the institutional ethical committee. Patients diagnosed with hypertensive disorders of pregnancy were evaluated and data was collected and analyzed. Results: Of the 1503 deliveries in the hospital during the period under review, 131(8.7%) were managed for hypertensive disorders of pregnancy. Pre-eclampsia was the commonest type of hypertensive disorder of pregnancy (69.3%) with the majority presenting with severe disease. Women of all age group were affected with highest incidence among 21-30years of age (69.4%). The incidence was maximum among primigravida (67.2%) compared to multipara 100 (32.8%). Intra uterine deaths were recorded among 12.2%, while a major share of fetus (41.2%) were diagnosed to have intrauterine growth retardation. Most common maternal complication in our study was abruption (7.6%), followed by HELLP (2.2%). Two maternal deaths were recorded, giving a case fatality rate of 1.5%. Conclusions: Hypertensive disorders of pregnancy are associated with high maternal and fetal morbidity and mortality. Regular antenatal follow up will help in early diagnosis and timely intervention of the cases. Also, special consideration and close surveillance of those women with early-onset disease is important. There is need for strengthening of communication and referral systems in the healthcare.